PENGARUH STRUKTUR CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN YANG MELAKUKAN INITIAL PUBLIC OFFERING (IPO) DI INDONESIA - Purwanto Purwanto; Sri Wahyu Agustiningsih (Universitas Sahid Surakarta, 2016)
This research aims to assess whether the corporate governance structure affect the company›s performance during the company conduct an Initial Public Offering (IPO) by using the period of 2002-2013. This study focuses on the effect of the structure of corporate governance on corporate performance. According to the results of previous research, the variables of corporate governance structure, namely the number of the members of the board of commissioners, the independence of board members, audit committee and auditors quality showed a significant effect on the company›s performance. This research is ekspost facto (causal comparative), namely the systematic empirical finding, which researchers can not control the independent variables because events have occurred since nature can not be dimanipulasi.Metode selection of samples used is purposive sampling and the sample used is 124 sample compa-nies conducting Initial Public Offering. This research uses multiple regression test model, using partial test and test simultaneously. Partial regression analysis results showed that the independence of the members of the board of commissioners and board members significantly affect the company›s performance. While simultaneously obtained results corporate governance structure significantly affect the level of performance of companies that conduct an Initial Public Offering (IPO) with the F value of 3.181 with a significance test amounted to 0,016. The significance value is less than the 0.05 level. For companies that did an IPO in the future, it is advisable to pay attention to the number of the members of the board of commissioners and the number of independent board members as in this study has a positive and significant impact on the performance of the company. For investors who will invest in the company›s IPO may notice the number of the members of the board of commissioners and the number of independent board members as it can be used as one of the consid-erations in investing. Investors will benefit if the company already has a board of directors and independent board